Software testing : - Everett, Gerald D. (John Wiley & Sons, 2007)
Software Testing delivers a thorough treatment of everything a technology professional needs to become a proficient software tester. The presentation sequence builds from simple to complex examples, giving noive readers a foundation for grasping the material. The use of real-world case studies further enhances understanding, while diagrams, tables, and sample printouts help the reader to visual the processes being discussed.